Enhancing de novo ceramide synthesis induced by bisphenol A exposure aggravates metabolic derangement during obesity - Gengfu Wang; Xu Hong; Jia Yu; Yuheng Zhang; Yuting Li; Zuo Li; Zhiyuan Zhu; Shaoyun Yuan; Xiaofei Zhang; Sheng Wang; Fuhai Zhu; Yong Wang; et al. (Elsevier, 2023)
Objective: Exposure to bisphenol A (BPA) has been shown to increase the prevalence of obesity and its related insulin resistance (IR). Ceramide is a sphingolipid known to facilitate the production of proinflammatory cytokines and subsequently exacerbate inflammation and IR during the progression of obesity. Here, we investigated the effects of BPA exposure on ceramide de novo synthesis and whether increased ceramides aggravate adipose tissue (AT) inflammation and obesity-related IR. Methods: A population-based case-control study was conducted to explore the relationship between BPA exposure and IR and the potential role of ceramide in AT in obesity. Next, we used mice reared on a normal chow diet (NCD) or a high-fat diet (HFD) to verify the results from the population study and then investigated the role of ceramides in low-level BPA exposure with HFD-induced IR and AT inflammation in mice treated with or without myriocin (an inhibitor of the rate-limiting enzyme in de novo ceramide synthesis). Results: BPA levels are higher in obese individuals and are significantly associated with AT inflammation and IR. Specific subtypes of ceramides mediated the associations between BPA and obesity, obesity-related IR and AT inflammation in the obesity group. In animal experiments, BPA exposure facilitated ceramide accumulation in AT, activated PKCζ, promoted AT inflammation, increased the expression and secretion of proinflammatory cytokines via the JNK/NF-κB pathway, and lowered insulin sensitivity by disrupting IRS1-PI3K-AKT signaling in mice fed a HFD. Myriocin suppressed BPA-induced AT inflammation and IR. Conclusion: These findings indicate that BPA aggravates obesity-induced IR, which is partly via increased de novo synthesis of ceramides and subsequent promotion of AT inflammation. Ceramide synthesis could be a potential target for the prevention of environmental BPA exposure-related metabolic diseases.